Laser droplet generation: Application to droplet joining - Govekar, E.; Jeric, A.; Weigl, M.; Schmidt, Michael (CIRP Annals - Manufacturing Technology, 2009)
In laser droplet joining, a drop of the desired size (≤1 mm) and temperature is generated on demand from a metal wire and deposited on a joining spot by a laser pulse. Droplet energy and volume are used to create a material-to-material joint. In this article, the laser droplet generation process, process parameters and a system for laser droplet generation and joining are described. Applicability of the novel laser droplet joining technology is demonstrated with various examples: spot joining of thin metallized parts, spot joining of dissimilar materials and continuous droplet joining of zinc-coated steel sheets. © 2009 CIRP.
Created from Fastlane, Scopus look-up
Keywords: Droplet; Joining; Laser